Ties that bind: motherhood, modernity, and the State in semi-colonial Egypt - Dhenin, Marianne (AUC Knowledge Fountain, 2020)
This thesis argues that a new institution of motherhood was constructed through modernizing reforms in the realms of law, public health, and social welfare in semi-colonial Egypt. Through the history of the institution of motherhood, I explore how colonialism, nationalism, and modernity penetrated family homes and affected women's daily lives. In Chapter One, I show that Egyptian women were blamed for the high infant mortality rate in turn-of-the-century Egypt. This coincided with an ongoing reorientation of the Egyptian family in popular and religious literature, wherein the woman was being recast as the central figure in shaping the child and tending the home. At the intersection of these phenomena, new discussions emerged about the significance of women as mothers and the proper way to perform motherhood as an Egyptian woman. I argue that an institution of motherhood was constructed and concretized through medical and legal reforms and the discussions surrounding them during this period. While Chapter One explores the construction of motherhood on the level of the population through medical and legal interventions that were opposable against women across Egypt, Chapter Two details several ways that motherhood was taught and enforced on the level of the individual in maternal and child welfare programs that sought to instruct women in a proper performance of motherhood. In Chapter Two, I argue that, with the foundation of the Ministry of Social Affairs in 1939 and subsequent legislation on the regulation of benevolent and social societies in Egypt, the State took increasing control over and began to depoliticize civil society. As the State started to tightly regulate and later to subsume maternal and child welfare programs that were operating in civil society, it extended its reach into women's homes and intimate matters of children and the family where it was able to access and therefore transform mothers and motherhood to an extent never before achieved. Throughout this thesis, I emphasize a conceptualization of modernization as a dialectical process. Modernization claims to liberate individuals, women, or a nation, but, at the same time, it creates elaborate structures for their discipline. The institution of motherhood is one such structure.